A grave in the woods - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series., 2024)
"Another entertaining and enlightening entry in the Bruno, Chief of Police series, featuring an archaeological dig in the French countryside that unearths World War II-era mysteries-all while Bruno dishes up more culinary magic When Abby, an American archaeologist, arrives in St. Denis on the heels of her divorce, she hopes to make a new life for herself as a specialist guide for visiting tourists. So when a local British couple discover a grave from World War II on their property, Abby is able to put her training to good use. As it turns out, in the grave are the remains of two German women and an Italian submarine officer who had a big secret to hide. The women are suspected of having had links to the German garrison in Bordeaux during the war. It's up to Bruno, just recovered from a gunshot wound earlier in the year, to unravel the mystery-and its contemporary relevance. His task is made more difficult by the horrible heat-dome summer, which is raising the temperature for miles around, as unprecedented amounts of rain drench the Massif Central and threaten increasingly dramatic floods. As Bruno drills to the heart of the case, matters get even more complicated when both Abby's financially distressed ex-husband and a mysterious dashing Italian naval officer arrive, with very different ideas in mind. Once again, Bruno is left to serve the guilty their just rewards, and his friends, some sumptuous Perigordian cuisine"--